A comparative study of mono-crystalline and poly-crystalline silicon solar cells under different climatic conditions of Bangladesh - Afifuzaman; Hossain, Mahmud; Rehan, Rubayet (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.